The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fmicb.2023.1159986
|View full text |Cite
|
Sign up to set email alerts
|

DegS protease regulates the motility, chemotaxis, and colonization of Vibrio cholerae

Abstract: In bacteria, DegS protease functions as an activating factor of the σE envelope stress response system, which ultimately activates the transcription of stress response genes in the cytoplasm. On the basis of high-throughput RNA sequencing, we have previously found that degS knockout inhibits the expression of flagellum synthesis- and chemotaxis-related genes, thereby indicating that DegS may be involved in the regulation of V. cholerae motility. In this study, we examined the relationships between DegS and mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…Compared with the NAC-group, the ability of the DdegS, DrpoE, and DrpoS strains to colonize the mouse intestine could be partially restored after the reduction of oxidative stress in the NAC+ group, but not to a level close to that of the wild-type, suggesting that adaptation to the oxidative stress environment is only a part of the V. cholerae's ability to colonize the intestine. The main reason for this is that in NAC untreated, the DdegS, DrpoE, and DrpoS mutant strains significantly reduced V. cholerae's ability to colonize the mice intestine, which is in agreement with our previous findings (Zou et al, 2023). However, in the present study, we also found that with and without NAC treatment, WT, DdegS:: degS, DdegSDrseA, DdegS+ pBAD24-rpoS, and DdegS+ pBAD24-xthA strains did not differ significantly in their ability to colonize the gut.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Compared with the NAC-group, the ability of the DdegS, DrpoE, and DrpoS strains to colonize the mouse intestine could be partially restored after the reduction of oxidative stress in the NAC+ group, but not to a level close to that of the wild-type, suggesting that adaptation to the oxidative stress environment is only a part of the V. cholerae's ability to colonize the intestine. The main reason for this is that in NAC untreated, the DdegS, DrpoE, and DrpoS mutant strains significantly reduced V. cholerae's ability to colonize the mice intestine, which is in agreement with our previous findings (Zou et al, 2023). However, in the present study, we also found that with and without NAC treatment, WT, DdegS:: degS, DdegSDrseA, DdegS+ pBAD24-rpoS, and DdegS+ pBAD24-xthA strains did not differ significantly in their ability to colonize the gut.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with the NAC untreated group, the colonization ability of the ΔdegS strain increased after NAC treatment, while there was no significant difference in the colonization ability of the ΔdegS +pBAD24- xthA strain, suggesting that the diminished colonization ability of the ΔdegS strain was only partially affected by the oxidative stress environment. XthA overexpression could eliminate the influence of oxidative stress, and could not revert to the influence of other factors, including motility, chemotaxis on intestinal colonization ( Zou et al., 2023 ).The differences with the Davies study may be due to the different strains we used and the different mice models.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, many studies have also found that cAMP-CRP could affect the virulence and colonization of V. cholerae through different regulatory ways. For example, according to Zou M. et al, DegS regulates V. cholerae's chemotaxis and motility through the cAMP-CRP-RpoS-FlhF pathway, which has an impact on the colonization of suckling mice intestines [28]. Muzhingi I et al demonstrated that V. cholerae controls the pathogenicity of interactions with arthropod hosts via the activity of the two-component CrbS/R system and cAMP-CRP activates the expression of the crbS and crbR genes [29].…”
Section: Discussionmentioning
confidence: 99%
“…The “ggplot2” R package was utilized to create a volcano plot, which illustrates the results. Furthermore, the “pheatmap” R package was employed to perform a bidirectional hierarchical clustering analysis of the collected DEGs (Xiantao tool, www.xiantao.com ) ( 12 ).…”
Section: Methodsmentioning
confidence: 99%